Potensi Terapeutik dari Metabolit Aktif Rimpang Jahe dalam Memodulasi Imunitas Tubuh terhadap Covid-19 - Dinda Afifa (Jurnal Ilmu Medis Indonesia, 2022)
Purpose: The purpose of this study was to determine the role of various active compounds in rhizome of ginger as an immunomodulator so that rhizome of ginger can be used to prevent and treat COVID-19. Currently, there are no specific therapies such as antiviral drugs that are relevant to treat COVID-19. However, herbal treatment is one of the efforts in handling this pandemic. Methodology: The method used is a literature review with the inclusion criteria of international scientific journals in the last ten years (2012-2021) which is accessed through trusted sites. Result: The results obtained are experimentally and clinically, ginger (Zingiber officinale rhizome) has shown various therapeutic activities, including anti-inflammatory, antioxidant, and immunomodulatory so it provides direct antiviral effects. Limitations: There is no precise identification of SARS-CoV-2 infection in the host organ and evaluation of the impact of ginger on virus-infected tissues. Contribution: Because of ginger can be used as a potential therapeutic ingredient, this study will contribute to preventing and treating COVID-19.